2010
DOI: 10.5194/acp-10-11647-2010
|View full text |Cite
|
Sign up to set email alerts
|

Light-absorbing impurities in Arctic snow

Abstract: Abstract. Absorption of radiation by ice is extremely weak at visible and near-ultraviolet wavelengths, so small amounts of light-absorbing impurities in snow can dominate the absorption of solar radiation at these wavelengths, reducing the albedo relative to that of pure snow, contributing to the surface energy budget and leading to earlier snowmelt.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
746
7
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(810 citation statements)
references
References 98 publications
(152 reference statements)
53
746
7
4
Order By: Relevance
“…These relatively high values could be due to previous sublimation or melt (Doherty et al, 2010). On 10 July, much higher BC concentrations were consistent with rapid BC enrichment once the snow began to melt.…”
Section: Spatio-temporal Variability In Surface Snow Bcmentioning
confidence: 57%
See 1 more Smart Citation
“…These relatively high values could be due to previous sublimation or melt (Doherty et al, 2010). On 10 July, much higher BC concentrations were consistent with rapid BC enrichment once the snow began to melt.…”
Section: Spatio-temporal Variability In Surface Snow Bcmentioning
confidence: 57%
“…Huang et al (2011) showed BC-in-snow concentrations decrease rapidly towards the northeast and away from major industrial regions. In the Arctic, Doherty et al (2010) and Forsstrom et al (2013) showed that the spatial differences in BC depended on the emission source intensity, the distance from the source to the deposition region, and the prevailing wind direction. In the eastern Sierra Nevada, Sterle et al (2013) noted that BC concentrations in aged snow were enhanced seven-fold relative to those in fresh snow.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported visible light absorption by non-BC particles (Yang et al 2009;Doherty et al 2010;Lack et al 2013). Doherty et al (2010) estimated that between 20% and 50% of the light absorption by particles in snowpack is caused by organic ("brown") carbon and dust.…”
Section: Uv/vis Spectrophotometermentioning
confidence: 99%
“…They probably evolved under natural selection to actively melt snow, thereby generating needed liquid in a frozen environment. Snow algae contrast with episodic deposition of non-living particulates, which sink into the snowpack if hydrophilic or non-polar, and remain atop a single season's melting snowpack if hydrophobic 33,34 . Because algae remain on the surface over much of the melt season and perennially resurface across melt seasons, they compound their effects over time.…”
Section: Implications For High-latitude Ice Sheetsmentioning
confidence: 99%